2011
DOI: 10.1002/asna.201111528
|View full text |Cite
|
Sign up to set email alerts
|

Extremely metal‐poor stars in SDSS fields

Abstract: Some insight on the first generation of stars can be obtained from the chemical composition of their direct descendants, extremely metal-poor stars (EMP), with metallicity less than or equal to 1/1000 of the solar metallicity. Such stars are exceedingly rare, the most successful surveys, for this purpose, have so far provided only about 100 stars with 1/1 000 the solar metallicity and 4 stars with about 1/10 000 of the solar metallicity. The Sloan Digital Sky Survey has the potential to provide a large number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
7
26
1
Order By: Relevance
“…This is not the estimate provided by the SDSS pipeline (Allende Prieto et al 2008), but the one obtained by our analysis of the SDSS spectra. This estimate has already been mentioned in our previous papers (Bonifacio et al 2011Caffau et al 2011c). It has been obtained from our code for automatic analysis Abbo (Bonifacio & Caffau 2003).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is not the estimate provided by the SDSS pipeline (Allende Prieto et al 2008), but the one obtained by our analysis of the SDSS spectra. This estimate has already been mentioned in our previous papers (Bonifacio et al 2011Caffau et al 2011c). It has been obtained from our code for automatic analysis Abbo (Bonifacio & Caffau 2003).…”
Section: Discussionmentioning
confidence: 78%
“…We could observe twelve stars in the g magnitude range 17 to 19, half of which have [Fe/H] < −3.5. In the sample, SDSS J102915+172927 happens to be the most metal-poor star known to date (Caffau et al 2011b); SDSS J174259+253135 shows no evident feature except the Ca ii-K line and the G-band; three stars are EMP and low in α-elements (SDSS J082511+163459 Caffau et al 2011c, SDSS J153346+155701, and SDSS J161956+170539); SDSS J135516+001319 is a metal-poor star that is very low in α-elements (Bonifacio et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing number of metal-poor stars in the literature that show similar low [X/Fe] ratios (Nissen & Schuster 1997;Spite et al 2000;Ivans et al 2003;Cayrel et al 2004;Honda et al 2004;Cohen & Huang 2010;Bonifacio et al 2011;Venn et al 2012;Caffau et al 2013a;Yong et al 2013a). They have been called "α-poor" or "Fe-rich" metal-poor stars.…”
Section: Skymapper Metal-poor Stars Of Interestmentioning
confidence: 99%
“…Figure 16 plots the element abundance pattern of SMSS J034249.53-284216.0 (cyan squares, cyan bold line), along with other stars exhibiting low [X/Fe] ratios in the literature, relative to the mean abundances from the SkyMapper sample 15 (Table 10). We restrict the literature stars in Figure 16 to have [Fe/H] 2 < − , though we note that many other "Feenhanced" stars exist in the literature at higher metallicities (e.g., Nissen & Schuster 1997;Ivans et al 2003;Cohen & Huang 2010;Bonifacio et al 2011;Venn et al 2012). As has been noted in the literature (e.g., Yong et al 2013a), there is some scatter in the abundances of these stars.…”
Section: Skymapper Metal-poor Stars Of Interestmentioning
confidence: 99%
“…With these data in hand we aim to calibrate the metallicity estimates obtained from the low-resolution SDSS spectra to obtain a better statistics of the metal-poor tail of the MDF. Our project is a spin-off of a pilot survey conducted using French and Italian guaranteed observing time on X-Shooter: a sample of twelve stars has previously been analysed by Bonifacio et al (2011);Caffau et al (2011bCaffau et al ( ,c, 2012, and Caffau et al (2013). In addition, other useful data for our purposes can be found in Bonifacio et al (2012), who analysed 16 EMP stars observed with UVES that were selected in a similar manner from SDSS; Spite et al (2013), who analysed three stars selected because they were C-enhanced; and Behara et al (2010), who analysed another set of three C-enhanced stars extracted from the SDSS.…”
Section: Topos Goalsmentioning
confidence: 99%